HOUSING LOANS AND PEOPLE'S BUSINESS LOANS AS DETERMINANTS OF RETURN ON ASSETS: AN EMPIRICAL STUDY ON PT BANK NEGARA INDONESIA (PERSERO) TBK MATOANGIN BRANCH OFFICE - Muhammad, Abbas; Salmah Harun; Muhammad Amin (Universitas Islam Lamongan, 2024)
This study aims to analyze the influence of Housing Loans (KPR) and People's Business Loans (KUR) on Return on Assets (ROA) at PT Bank Negara Indonesia (Persero) Tbk Matoangin Branch Office. KPR and KUR were chosen because of their strategic role in supporting the housing sector and micro, small, and medium enterprises (MSMEs) in Indonesia. The data used is secondary data from the bank's financial statements for the period 2017-2022. The research method used is a quantitative approach using multiple linear regression analysis in SPSS. The results of the analysis show that both KPR and KUR have a positive and significant influence on bank ROA. The regression coefficient shows that each unit of increase in the mortgage will increase the ROA by 152,912, while the KUR will increase the ROA by 110,033, assuming the other variables are constant. The determination coefficient test showed that the regression model was able to account for about 96.5% of the variation in ROA, showing a good match between the model and the existing data. These results make a theoretical and practical contribution in understanding the effectiveness of KPR and KUR as instruments to improve bank financial performance. This research is expected to be a reference for bank management in optimizing credit distribution policies to support economic growth and increase company profitability. These findings also have the potential to provide input for further research in the context of the use of microcredit and housing in Indonesia.